2013
DOI: 10.2147/ijgm.s49701
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid hyperemesis syndrome with extreme hydrophilia

Abstract: Marijuana is the most widely used recreational drug in the US. Hyperemetic hydrophilic syndrome is a previously described but infrequently recognized condition of cannabinoid abuse with hyperemesis and obsessive hot showering. We present a 47-year-old male known marijuana addict with intractable abdominal pain who could not wait for physical examination, meal, or medication, because of obsessive compulsive warm baths. He had a history of epilepsy and addiction to marijuana, which he took on the day of admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…The patient found that hot water relieved his symptoms better than anything else. After 3 days in the hospital (and no marijuana use), his symptoms resolved [94]. It should be noted that in the case of CHS, compulsive showering in hot water is not an anxiety disorder but rather a learned behavior that the patient develops to relieve symptoms [94].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient found that hot water relieved his symptoms better than anything else. After 3 days in the hospital (and no marijuana use), his symptoms resolved [94]. It should be noted that in the case of CHS, compulsive showering in hot water is not an anxiety disorder but rather a learned behavior that the patient develops to relieve symptoms [94].…”
Section: Resultsmentioning
confidence: 99%
“…After 3 days in the hospital (and no marijuana use), his symptoms resolved [94]. It should be noted that in the case of CHS, compulsive showering in hot water is not an anxiety disorder but rather a learned behavior that the patient develops to relieve symptoms [94]. Similar to hot water, capsaicin provides symptomatic relief of CHS [95-97] but not other vomiting disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CB1 receptors are also located on peripheral enteric nerves, and their stimulation lead to slow gastrointestinal transit. CB1 receptors are also found in the hypothalamus close to the thermoregulatory center which could explain the role of compulsive hot bathing in relieving symptoms, this has been thought to be related to counteraction of cannabis effect at the thermoregulatory center (6)(7)(8).…”
Section: Case Presentationmentioning
confidence: 99%
“…Care during the chronic maintenance phase involves prevention of relapse and patient education of the condition to help them understand cannabinoid substance use as the cause of their symptoms. Other measures to prevent relapse include cognitive behavioral therapy and drug rehabilitation programs (7)(8)(9).…”
Section: Case Presentationmentioning
confidence: 99%